On the role of chemical banding and austenite grain size in microstructure evolutions and phase transformation kinetics of gear steels. (21st November 2022) - Zhao, Yina; Chen, Yinli; Zuo, Xiaojian; Yu, Wei; Qiu, Lei; Luo, Zhuzheng; Sun, Jiquan
Graphical abstract: Mechanism of banded structure evolution during cooling at small or large austenite grain sizes. Highlights: The banded structure is eliminated when the austenite grain size is smaller than the element segregation banding width. Si and Mo promote α/γ interfacial migration, while Cr, Ni and Mn inhibit α/γ interfacial migration. The most serious segregation of Cr and Mn lead to the largest critical austenite grain size of 22CrMo. Abstract: Defects in the banded structure of low-carbon gear steel significantly limit the application of gears in the construction industry. Therefore, the banded structure in the gear steel must be eliminated. In this study, the content and segregation banding width of Si, Mo, Cr, Mn, and Ni, phase distribution, austenite grain size, and hardness were characterized using electron probe microanalysis, laser scanning confocal microscopy, electron backscatter diffraction, and Vickers indenter. Element diffusion and α/γ interfacial migration were calculated using the Thermo-Calc analysis and simulation methods. The results showed that the best mechanical properties experimental steels without banded structures can be obtained during heating at 1300 °C for 2 h, 1250 °C for 1 h, and 1150 °C for 2 h for 20CrNiMo, 22CrMo, and 20CrMnTi, respectively. Under the critical hot-rolling process of eliminating the banded structure, the ferrite transformation temperature difference ΔAr3 and ferrite transformation interval (Ar3 -Bs) of the 22CrMo sample were the largest. Si and Mo promoted interfacial migration, whereas Cr, Mn, and Ni inhibited interfacial migration. The interfacial migration speed of 22CrMo is the highest. The interfacial migration distance of the 22CrMo sample was the longest, and the final interfacial migration distance of 20CrMnTi was the shortest. When the migration position of the α/γ interface was less than 65 % of the system's total size, the ferrite-banded structure disappeared. The critical austenite grain sizes of 20CrNiMo, 22CrMo, and 20CrMnTi were 31.6, 35, and 22.2 μm, respectively. The banded structure is eliminated when the austenite grain size is smaller than the element segregation banding width. When eliminating the banded structure, the interfacial migration distance of 22CrMo was the longest and its critical austenite grain size was the largest.